(untitled) (Orkopata. Revista de Lingüística, Literatura y Arte, 2022)
The Mapuche-Williche sought an equal relationship between each society in spite of the conquest of their territory, as well as they sought that the Hispanic-Creole don’t interfere in their internal affairs. This means that they tried to establish equal intercultural relationships but in reality, societies were asymmetric, considering that Chilean Hispanic-Creole’s authorities pegged themselves as rulers. Public speeches of Mapuche-Williche’s resistance, as so-called "memorials", have appeared since the late nineteenth century and let us observe the search of equal relationship in the public sphere. But, before observing the emergence of those memorials as discourse of resistance, we must observe the process that allowed them to appear. This paper seeks to build part of the genealogy of the Mapuche-Williche’s memorials based on the letters they sent to those previously pleaded authorities in the Fütawillimapu during the nineteenth century.